Deux théories de la faute en responsabilité médicale - Léger-Riopel, Nicholas (Comparative Legilinguistics, 2025)
This article seeks to elucidate the dual conceptions or theories of fault that exist in the domain of medical liability law. The first of these is often characterized as "descriptive" or "customary," as appears from a survey of relevant jurisprudential and doctrinal sources, However, this predominant understanding of medical malpractice is increasingly facing scrutiny as a second conception emerges. This alternative perspective is manifested through the development, across various jurisdictions, of a normative lexicon—specifically the term "reasonableness"—which delineates the legal standard anticipated of a physician's conduct, In addition to the oversight exercised by the exclusion of customary practices that may exhibit evident deficiencies or hazards, contemporary courts have also been entrusted with the critical function of acting as "guatekeepers " of the quality of scientific evidence required to evaluate the propriety of medical practices. This article further delves into specific concerns and ambiguities related to the evidentiary aspects of establishing a customary standard. Such uncertainties, we conlude, will in turn perpetuate a standard that is still essentially grounded in established custom and clinical practices.